Redefining “Sacred” through the Indigenous Religion Paradigm: Case Study of Sunda Wiwitan Community in Kuningan - Fany Nur Rahmadiana Hakim (Religio: Jurnal Studi Agama-agama, 2022)
The definition of sacred in the World Religions paradigm is limited to the things that have to do with the symbolization of spirituality. Oftentimes, the sacred value which is not in accordance with the characteristics required by the World Religions paradigm is considered as something non-religious. In terms of preserving nature, based on the findings, many scholars have proven that indigenous people have their own value in interpreting the sacred. By attaching the sacred word to the realm where they live, it is not merely a matter of ownership or a place where they practice religious rituals. The Sunda Wiwitan community in Kuningan is one model that still carries out the tradition of ancestral heritage which they apply to the ecological aspect by the forest zoning and having a special place, namely Leuweung Leutik, a sacred little forest which for them is not only a place to perform rituals, but also as a means of preserving nature. Through the paradigm of Indigenous Religions, in which indigenous people have a strong connection with nature and recognize the subjectivity of nature as coequal living things, they are able to treat nature as they benefit from nature. This paper examines how the paradigm of Indigenous Religion is able to give new meaning to what is the sacred, which in this regard they apply to customary forest management. With a qualitative research approach using mixed data collections: secondary data and in-depth interviews, this paper explains new ideas obtained from the local knowledge of the Sunda Wiwitan community in Kuningan in order to protect their sacred place.